1987
DOI: 10.1002/1097-0142(19871015)60:8<1883::aid-cncr2820600835>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent carcinoma in congenital dilatation of the bile duct and anomalous arrangement of the pancreatico-bile duct: Carcinogenesis of coexistent gall bladder carcinoma

Abstract: From 197'2 to 1985, 40 cases of congenital dilatation of the bile duct (CDBD) were experienced in the department of the authors. Those consisted of 19 cases of anomalous arrangement of the pancreaticobile duct (P-B anomaly), five of bile duct carcinoma, and two of gall bladder carcinoma. In addition, four patients who showed no dilatation of the bile duct in spite of the presence of a P-B anomaly were experienced, and coexistent gall bladder carcinoma was present in three of four cases. The incidence of bile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 6 publications
1
22
1
Order By: Relevance
“…Intestinal metaplasia of the common bile duct and gallbladder was seen in 20% of the cases, and the severity of the epithelial changes was proportional to the duration of the experiment (9). In humans, an increased incidence of carcinoma has been shown in patients with an anomalous choledochopancreatic junction that is associated with intestinal metaplasia (10). In this study, however, we were unable to find foci of dysplasia in the metaplastic areas; therefore, the possibility that the tumor induced the metaplastic changes cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal metaplasia of the common bile duct and gallbladder was seen in 20% of the cases, and the severity of the epithelial changes was proportional to the duration of the experiment (9). In humans, an increased incidence of carcinoma has been shown in patients with an anomalous choledochopancreatic junction that is associated with intestinal metaplasia (10). In this study, however, we were unable to find foci of dysplasia in the metaplastic areas; therefore, the possibility that the tumor induced the metaplastic changes cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The early changes in the gallbladder mucosa of patients with AAPBD leading to carcinogenesis are unclear. Major histopathologic findings in several studies of this Tokiwa et al: Cell proliferation in pancreaticobiliary anomaly anomaly included coexistent metaplastic changes of the gallbladder mucosa 6,22,23. These changes were found not only in cancerous but also in noncancerous areas.…”
Section: Early Changes In Gallbladder Epitheliummentioning
confidence: 95%
“…Gallbladder carcinoma is associated with AJPBD in approximately 10% of patients. In this regard, several investigations revealed that among AJPBD patients without a dilatation of common bile duct, the incidence of gallbladder carcinoma is higher than in those with choledochal cyst, a cystic dilatation of common bile duct [35,36,37].…”
Section: Anomalous Junction Of the Pancreaticobiliary Ductmentioning
confidence: 99%